2009
DOI: 10.1007/s12540-009-0615-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trioctyl Phosphate and Cresyl Diphenyl Phosphate as flame-retarding additives for Li-Ion battery electrolytes

Abstract: Safety concerns related to lithium-ion batteries have been the key obstacle to their application in hybrid electric vehicles. Trioctyl Phosphate (TOP) and Cresyl Diphenyl Phosphate (CDP) were studied as potential flame-retarding additives for lithium-ion batteries. The electrochemical performance and thermal stability of the additive-containing electrolytes, in combination with a cell comprising a LiCoO2 cathode and Mesocarbon Microbeads (MCMB) anode, were tested in coin cells. Cyclic Voltammetry (CV), Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Trioctyl phosphate (TOP) and tris (2-ethylhexyl) phosphate (TEHP), which are linear and branched structural isomer of phosphate ester, are known as an additive that helps the electrolyte improve its wettability of the separator. 18,19 However, regarding TOP, as reported in a previous work by Shim et al, 20 adding even 5 wt% of TOP causes a significant decrease in rate and cycling performance, probably due to the increase in cell impedance. In addition, although TEHP has an advantage of the high flash point of 200 °C, TEHP has a very high viscosity of 12 mPa s (Table I), so even a small added amount may have the problem of raising the viscosity of the electrolyte.…”
mentioning
confidence: 88%
“…Trioctyl phosphate (TOP) and tris (2-ethylhexyl) phosphate (TEHP), which are linear and branched structural isomer of phosphate ester, are known as an additive that helps the electrolyte improve its wettability of the separator. 18,19 However, regarding TOP, as reported in a previous work by Shim et al, 20 adding even 5 wt% of TOP causes a significant decrease in rate and cycling performance, probably due to the increase in cell impedance. In addition, although TEHP has an advantage of the high flash point of 200 °C, TEHP has a very high viscosity of 12 mPa s (Table I), so even a small added amount may have the problem of raising the viscosity of the electrolyte.…”
mentioning
confidence: 88%
“…Phosphorous additives may not be as effective as the halogenated ones, but they are less toxic and more environmentally friendly. Examples of such additives include alkyl phosphates [87,115,164], aryl phosphates [43, 117,133,176], mixed alkyl aryl phosphates [95,114], alkyl phosphites [97,164], alkyl phosphonates [148], phosphonamidate [51], phosphazenes [5,40], and some other phosphorous compounds [141,175]. Halogenated phosphorous additives have primarily been fluorinated ones, as many of the fluorinated alkyl solvents themselves are non-flammable.…”
Section: Flame Retardant Additivesmentioning
confidence: 99%
“…Morita et al (2005) showed that TMP perhaps achieves this benefit by preventing thermal decomposition of LiPF 6 . Cresyl diphenyl phosphate (CDP) FRs have been studied by Shim et al (2009), as well as by Zhou et al (2008). Both groups showed that the thermal stability and non-flammability of aprotic liquid electrolytes can be markedly improved by adding only 5wt% CDP.…”
Section: Additives For Aprotic Liquid Electrolytesmentioning
confidence: 99%